A new species of Gastrochilus (Aeridinae, Vandeae, Orchidaceae) and a new record species from Yunnan, China - Liu, Qiang; Tan, Yun-Hong; Gao, Jiang-Yun (Phytotaxa, 2016)
Although Gastrochilus Don (1825:32) is a small genus, its generic and interspecific relationships are still not well understood (Seidenfaden1988, Tsi 1996, Pridgeon et al. 2014, Zou et al. 2015). It comprises 64 species collectively distributed from China, India and Sri Lanka through eastern Asia and southern Japan to Indonesia and the Philippines (Kumar et al. 2014, Govaerts et al. 2015, Raskoti 2016). China is the centre of species diversity for the genus, which contains 39 species, 19 of which are believed to be endemic (Tsi 1999, Chen et al. 2009, Yi et al. 2012, Kumar et al. 2014). During our field investigation in southeastern Yunnan, two unusual species of this genus were discovered. After undertaking a comprehensive literature and herbarium review, these two species were identified as G. sect. Gastrochilus Don (1825: 32), which is characterized by stout stem with large cauline leaves. One is a new record for China, and the other is the new species.